Psychology of conspiracy theories - Prooijen, Jan-Willem van. (New York Routledge, 2018)
Conspiracy thinking? ? the search for explanations of significant global events in clandestine plots, suppressed knowledge and the secret actions of elite groups ? provides simple and logical answers to the social doubts and uncertainties that occur at times of major national and international crises. Contemporary social psychology seeks to explain the human motivation to create, share and receive conspiracy theories, and to shed light on the consequences of these theories for people?s social and political functioning.
Includes bibliographical references.
Keywords: Conspiracy theories